Gambaran Tingkat Pengetahuan Orang Tua dalam Pemberian Asi Eksklusif pada Bayi Usia 0-6 Bulan di Desa Ngaru-Aru dan Desa Trayu Kecamatan Banyudono Kabupaten Boyolali - Della Novinda Suyamto; Mulyaningsih Mulyaningsih (STIKes Ibnu Sina Ajibarang, 2024)
Background: Mothers' lack of understanding and knowledge about breastfeeding and the benefits of breastfeeding are the biggest factors that make parents easily influenced and switch to formula milk. Non-exclusive breastfeeding carries a risk of death due to diarrhea. There are several factors that can influence the success of exclusive breastfeeding, namely age, education, and parents' knowledge about exclusive breastfeeding. Objective: To determine the level of knowledge of parents in providing exclusive breastfeeding to babies at the Banyudono I Community Health Center. Method: Descriptive. The sampling technique was 41 pairs of parents who had babies in the working area of ​​the Banyudono I Community Health Center. Results: Univariate test results show the characteristics of respondents: fathers aged >35 years (53.7%) mothers aged 20-35 years (73.2%), Most of the fathers had a high school education, 30 respondents (73.2), mothers with a high school education, 26 respondents (60.7%), Fathers work as private employees, 33 respondents (80.5%), mothers as housewives, 22 (53.7%), and fathers' knowledge levels are in the good category, 34 respondents (82.9%), mothers' knowledge levels are good, 34 respondents (82.9%). Conclusion: The majority of parents' knowledge level in providing exclusive breastfeeding to babies aged 0-6 months is good, 82.9%.